Pengaruh Motivasi Dan Lingkungan Belajar Terhadap Hasil Belajar Siswa Pada Kelas XI MPLB Mata Pelajaran Ekonomi Bisnis SMK Negeri 6 Kupang - doren, yosefina beto; abolladaka, jacob; Br Simanungkalit, Erika Feronika (Journal Economic Education, Business and Accounting, 2023)
This research was conducted in class XI MPLB SMK Negeri 6 Kupang which has low student learning outcomes. The purpose of the research is to determine the impact of learning motivation and learning environment on the learning outcomes of grade XI MPLB students. The strategy used in this quantitative research method is associative causal. The observation population was 61 students, while the sample for this observation consisted of 53 students of class XI MPLB. Data was collected by means of a questionnaire of 32 statements. Based on the results of data analysis, t count = 9.949 and t table = 2.008. This means that 9,949>2,008, so that the H1 submitted can be accepted, namely the results of learning business economics students at SMK Negeri 6 Kupang are influenced by their learning motivation, 9,588>2,008 which means that the learning environment is compared with student learning outcomes in business economics subjects at SMK Negeri 6 Kupang, where the H2 submitted can be accepted, In addition, the estimated value for the F test is 251,039 > Ftable 3,182, with significance levels of 0.00 < 0.05. So it can be said if H3 is accepted or learning motivation and learning environment simultaneously have an impact on learning outcomes.